The hole story of the doughnut - Miller, Pat, 1951 May 28- (Houghton Mifflin Harcourt, 2016)
"In 1843, 14-year old Hanson Gregory left his family home in Rockport, Maine and set sail as a cabin boy on the schooner Achorn, looking for high stakes adventure on the high seas. Little did he know that a boat load of hungry sailors, coupled with his knack for creative problem-solving, would yield one of the world's most prized pastries. At long last, here's the hole truth about the invention of the donut!"--